MORPHOFUNCTIONAL CHARACTERISTICS OF THE HYMEN IN GIRLS IN THE AGE CATEGORIES OF SECOND CHILDHOOD IN THE UZBEK POPULATION (Uzbekistan Open Conference, 2025)
In girls in the second childhood age group (8–11 years), the hymen was characterized by annular, oval, round-oval, and crescent-shaped shapes with a slightly stretchable consistency. The average hymenal parameters in girls in the Uzbek population during the first childhood were: hymenal wall height 0.4 (medium height), wall thickness 0.1 (thin), and hymenal opening size 1.0 (small). In girls in the second childhood age group, these parameters were: hymenal wall height 0.4 (medium height), wall thickness 0.2 (thin), and natural opening size 1.15 (medium).